(untitled) (Eurasian Research Bulletin, 2022)
In this article, we are talking about problems and their solution using information and communication technologies in education. The advantages of software for the creation of educational content for e-learning and the programs that organize the educational process are shown, which provide for the improvement of the quality of education with use in the educational process